Novel MYBPC3 Mutations in Indian Population with Cardiomyopathies - Rani DS; Kasala A; Dhandapany PS; Muthusami U; Kunnoth S; Rathinavel A; Ayapati DR; Thangaraj K (Dove Medical Press, 2023)
Deepa Selvi Rani,1 Apoorva Kasala,1 Perundurai S Dhandapany,2 Uthiralingam Muthusami,3 Sreejith Kunnoth,3 Andiappan Rathinavel,4 Dharma Rakshak Ayapati,5 Kumarasamy Thangaraj1,6 1Department of Population and Medical Genomics, CSIR-Centre for Cellular and Molecular Biology, Hyderabad, Telangana, India; 2Department of Cardiovascular Biology and Medicine, Institute for Stem Cell Science and Regenerative Medicine, Bangalore, Karnataka, India; 3Department of Advanced Zoology and Biotechnology, Loyola College, Chennai, Tamil Nadu, India; 4Department of Cardiology, Government Rajaji Hospital, Madurai, Tamil Nadu, India; 5Department of Cardiology, Nizam's Institute of Medical Sciences, Hyderabad, Telangana, India; 6DBT-Centre for DNA Fingerprinting and Diagnostics, Hyderabad, Telangana, IndiaCorrespondence: Deepa Selvi Rani; Kumarasamy Thangaraj, CSIR-Centre for Cellular and Molecular Biology, Uppal Road, Hyderabad, 500 007, India, Tel +91-40-271926, Email deepa@ccmb.res.in; thangs@ccmb.res.inBackground: Mutations in Myosin Binding Protein C (MYBPC3) are one of the most frequent causes of cardiomyopathies in the world, but not much data are available in India.Methods: We carried out targeted direct sequencing of MYBPC3 in 115 hypertrophic (HCM) and 127 dilated (DCM) cardiomyopathies against 197 ethnically matched healthy controls from India.Results: We detected 34 single nucleotide variations in MYBPC3, of which 19 were novel. We found a splice site mutation [(IVS6+2T) T>G] and 16 missense mutations in Indian cardiomyopathies [5 in HCM; E258K, T262S, H287L, R408M, V483A: 4 in DCM; T146N, V321L, A392T, E393K and 7 in both HCM and DCM; L104M, V158M, S236G, R272C, T290A, G522E, A626V], but those were absent in 197 normal healthy controls. Interestingly, we found 7 out of 16 missense mutations (V158M, E258K, R272C, A392T, V483A, G522E, and A626V) in MYBPC3 were altering the evolutionarily conserved native amino acids, accounted for 8.7% and 6.3% in HCM and DCM, respectively. The bioinformatic tools predicted that those 7 missense mutations were pathogenic. Moreover, the co-segregation of those 7 mutations in families further confirmed their pathogenicity. Remarkably, we also identified compound mutations within the MYBPC3 gene of 6 cardiomyopathy patients (5%) with more severe disease phenotype; of which, 3 were HCM (2.6%) [(1. K244K + E258K + (IVS6+2T) T>G); (2. L104M + G522E + A626V); (3. P186P + G522E + A626V]; and 3 were DCM (2.4%) [(1. 5'UTR + A392T; 2. V158M+G522E; and 3.V158M + T262T + A626V].Conclusion: The present comprehensive study on MYBPC3 has revealed both single and compound mutations in MYBPC3 and their association with disease in Indian Population with Cardiomyopathies. Our findings may perhaps help in initiating diagnostic strategies and eventually recognizing the targets for therapeutic interventions.Keywords: MYBPC3, cardiomyopathy, sarcomere genes, HCM, DCM